Simple phantom fabrication for MRI‐based HDR brachytherapy applicator commissioning - Fagerstrom, Jessica M. (J Appl Clin Med Phys, 2020)
A new high dose rate (HDR) brachytherapy program was initiated in a community hospital setting, with the goal of using magnetic resonance (MR) images with the implant in place during the planning process. Physics acceptance testing and commissioning was completed for key program components, including multiple applicators. To image new applicators for MRI‐based planning prior to use with patients, agar gel doped with copper sulfate was created using simple, MR‐safe household materials as a practical and inexpensive alternative to custom‐machined precision phantoms. Applicators in‐phantom were scanned in a 1.5 T MRI scanner using the same sequences developed for the brachytherapy program, then rigidly registered to high‐resolution computed tomography (CT) images to assess distortion, artifact, and geometric displacement. To date, Varian tandem and ring sets, segmented cylinders, cervical probes, endometrial applicators; and third‐party plastic needles, tandems, and vaginal guides have been imaged in phantom and are available for use clinically.